Synchronous BRCA2 positive ovarian carcinoma with ALK positive NSCLC: Double trouble - Ullas Batra; Shrinidhi Nathany; Mansi Sharma; Anila Sharma; Sunil Pasricha; Vidya Menon; Joslia T. Jose; Anurag Mehta (Elsevier, 2022)
Lung cancer being a molecularly distinct entity in the female population, multiple primary tumors including the genital and urinary tract malignancies with lung carcinoma is rare and constitutes a unique set of patient population. This case report serves to illustrate the rarity of multiple primary tumor involving ovarian carcinoma with ALK positive lung cancer. Additionally high throughput sequencing revealed a germline BRCA2 mutation causing alteration of splice site. This report highlights the occurrence of multiple primary tumors in this patient possibly due to BRCA2 predisposition.